Valuing quality - Laura Blow; Ian Crawford (Institute for Fiscal Studies (IFS), 1999)
This paper uses revealed preference restrictions and nonparametric statistical methods to bound a quality-constant price series for a good that changes quality over time. Unlike the more usual hedonic regression techniques for estimating quality-adjusted prices, this method does not require us to observe the changing characteristics of the good or to assume a particular functional relationship between these characteristics and quality. To place a bound on quality change using revealed preference conditions we assume that preferences are stable over time, that quality change occurs in one good or group of goods and that the direction of quality change is known.
Keywords: C43; D11; 330